No School for Eze - Okoye, Ifeoma (Kachifo Limited, 2007)
Eze did not like school. One morning when it was time for Eze to go to school, he began to cry. ''Mummy, let me stay at home with you toda,'' Eze said. ''No Eze, you should go to school and learn to read and write,'' Mummy said$1! = s
Keywords: Adventure; Juvenile Fiction